Utilization of the Unversity’s Official Website for Environmental Education - Saputri, Kirana Fimelya; Kartikasari, Mei Candra; Hasan, Muchammad Maulana; Hakim, Muhammad Nu'man; Yuliana, Yohanes Gatot Sutapa (Letters in Information Technology Education (LITE), 2019)
Indonesian public awareness about the importance of the environment is still quite low. For example, concern about cleanliness which will have an impact on the environment and health, so it is important to encourage environmental care activities. The University Level Educational Institution was chosen because students have a very important role, namely as one of the Agent of Change that is expected to be able to bring better change to Indonesia's change. This study aims to determine how the role of the official website of the university in Indonesia on the educational environment. With this study will be known how much the level of awareness of the importance of environmental education in a university environment in Indonesia. Based on the results of the study.